Cryptotanshinone and tanshinone IIA from Salvia milthorrhiza Bunge (Danshen) as a new class of potential pancreatic lipase inhibitors. Issue 5 (4th March 2021) - Marrelli, Mariangela; Grande, Fedora; Occhiuzzi, Maria Antonietta; Maione, Francesco; Mascolo, Nicola; Conforti, Filomena
Abstract: Salvia miltiorrhiza Bunge extract was investigated for the first time for its inhibitory activity against pancreatic lipase (PL), an important enzyme involved in the digestion of dietary fats. It showed a concentration-dependent activity with an IC50 value of 3.54 ± 0.22 mg/mL. Two compounds, cryptotanshinone and tanshinone IIA (the major lipophilic constituents of S. miltiorrhiza ), have been selected as potential ligands of PL. Cryptotanshinone showed a higher lipase inhibitory activity (IC50 = 6.86 ± 0.43 µM) compared to the parent tanshinone IIA. Molecular docking studies were undertaken to establish whether a direct interaction of the principal constituents of the S. miltiorrhiza extract with the human pancreatic lipase could be evoked. All these findings provided new insights into the understanding of the interactions between natural constituents of S. miltiorrhiza extract and PL, also suggesting that cryptotanshinone could be used as lead compound for the development of efficacious PL inhibitors. Abstract :